Multi-source solid waste synergistically activated fine particle grade tailings self-gluing filling material and preparation method thereof

By using a multi-source solid waste synergistic activation method, a high-alkali-sulfate synergistic activation system is formed by water-quenched slag, desulfurized gypsum and alkaline activator to activate the activity of fine-grained tailings and generate CSH gel and ettringite. This method solves the problems of high cost, high carbon emissions and low strength of traditional backfill materials, and achieves high-strength cementation with low cost and low carbon emissions, which is suitable for mine backfilling projects.

CN122464679BActive Publication Date: 2026-11-06NORTHEASTERN UNIV CHINA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610953916.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-30
Publication Date
2026-11-06
Estimated Expiration
2046-06-30

AI Technical Summary

Technical Problem

Existing backfill materials cannot simultaneously meet the requirements of low cost, low carbon emissions, wide particle size compatibility, and high bonding strength. Traditional technologies have failed to effectively activate the activity of fine-grained tailings, resulting in high cement consumption, high cost, low early strength, easy structural collapse, and high carbon emissions, which contradicts the concept of green mining development.

Method used

A multi-source solid waste synergistic activation method is adopted to form a high-alkali-sulfate synergistic activation system by water-quenched slag, desulfurized gypsum and alkaline activator, which activates the pozzolanic activity of fine-grained tailings, generates CSH gel and ettringite, realizes the self-cementation of fine-grained tailings, and forms a dual consolidation structure of chemical bonding and physical filling.

Benefits of technology

It achieves high-strength bonding with low cost and low carbon emissions, has a wide range of applications, is easy to construct, meets the needs of mine backfilling projects, improves the utilization rate of solid waste resources and the universality of projects, and solves the problems of high cost, high carbon emissions and low strength of traditional backfilling materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122464679B_ABST
    Figure CN122464679B_ABST
Patent Text Reader

Abstract

The application discloses a kind of multi-source solid waste synergistic excitation fine particle grade tailings self-cemented filling material and preparation method thereof, it is related to the technical field of mine filling material, to solve the problem of narrow applicable particle size range of traditional solid waste base filling material, cementing strength is insufficient.The application includes cementing material, fine particle grade tailings and water are mixed and stirred according to design sand ratio, obtain self-cemented filling body, form high-strength backfill after curing.Cementing material includes water quenching slag, desulfurization gypsum and quicklime.Core cementing mechanism is: using the alkalinity provided by quicklime and calcium source, excite active silica-aluminum component in water quenching slag and the pozzolanic activity of tailings itself, reaction generates hydration product system mainly with C-S-H gel and ettringite;Through the dual consolidation effect of chemical bonding and dense filling, firm interface bonding is formed between cementing material and fine particle grade tailings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of mine backfill materials, specifically a fine-grained tailings self-cementing backfill material that is synergistically activated by multiple sources of solid waste. Background Technology

[0002] Fine-grained tailings are a major solid waste generated from mineral processing. They are stored in large quantities and have limited disposal channels. Open-air storage not only occupies land but also easily causes safety and environmental problems such as tailings dam failure, dust, and heavy metal leakage. This type of tailings has fine particles, high moisture content, and is difficult to dewater. It has poor storage stability and poses more prominent safety hazards. Its large-scale safe disposal has become an urgent problem to be solved in the mining industry. Mine backfilling is the mainstream method for disposing of tailings and managing goaf areas. Currently, ordinary Portland cement is commonly used as a cementing material. However, this approach has significant drawbacks: the large cement content and high cost ratio significantly increase backfilling costs, hindering the large-scale application of fine-grained tailings backfilling; the weak interfacial bonding between cement and fine-grained tailings results in low early strength and easy structural collapse of the backfill, requiring increased cement usage or complex pretreatment processes such as flocculation, filtration, and dewatering on-site, leading to a vicious cycle of "paying for incompatible materials with expensive and complex processes"; at the same time, cement production has high carbon emissions, which contradicts the dual-carbon development concept, creating an irreconcilable structural contradiction between traditional cement-based systems and fine-grained tailings.

[0003] Existing publicly available solid waste-based tailings backfill materials also have significant technical shortcomings: Patent CN112851286A discloses a method for backfilling gold tailings using water-quenched slag, lime, gypsum, and mirabilite as cementing powder. Regarding tailings particle size, this method strictly limits its applicable fine-grained tailings particle size to below 0.038 mm. Even with a full tailings solution, the yield of ultrafine particles smaller than 0.038 mm is only 32-35%. Because the cementing mechanism of this method remains at the level of traditional external cementitious material physically coating inert aggregates, it does not utilize the pozzolanic activity of the tailings themselves. Furthermore, coarse tailings have a small specific surface area and few surface active sites, making it difficult for the hydration products of the cementing material to form a uniform coating and effective bond on their surface. When the tailings particle size exceeds 0.038 mm, the area of ​​cementing material required per unit mass of tailings decreases sharply, and the interfacial bonding strength is significantly weakened. This means that when the fine-grained content in the tailings is even lower or the particles are coarser, the cementing effect of this method is difficult to guarantee, resulting in a narrow range of applications.

[0004] Regarding the cementation mechanism, the technical approach of this scheme remains at the level of physical encapsulation of aggregates by external cementitious materials. It simply mixes cementitious powder with tailings and relies on the cementitious products formed after the cementitious powder is hydrated to encapsulate the tailings particles. The tailings themselves only serve as inert filler aggregates, and the aluminosilicate minerals on the surface of the particles are not activated to participate in the hydration reaction. Therefore, there is a lack of direct chemical bonding between the cementitious materials and the tailings. Even with the quicklime content increased to 5-15 wt%, self-cementing cannot be achieved. The fundamental reason lies in the inherent physicochemical mismatch between the specified ultrafine tailings (<0.038 mm) and the high-lime, high-alkali system. The ultrafine tailings have extremely high specific surface area and surface activity, which triggers instantaneous, heterogeneous supersaturated precipitation in a high-alkali, high-calcium environment. This rapidly forms a dense passivation shell of hydration products on the particle surface, physically blocking the continuous dissolution and ion migration of internal active silica-alumina components, thus severing the deep foundation of chemical bonding. Simultaneously, the high ionic strength exacerbates the soft agglomeration among the ultrafine tailings, disrupting the initial packing density of the slurry and causing microcracks to proliferate in the interfacial transition zone, macroscopically manifesting as strength reduction and structural loosening. Therefore, the characteristics of the ultrafine tailings selected in this application inherently conflict with the core activation system of this invention at the thermodynamic and kinetic levels. Tailings within this particle size range lack the physicochemical basis for effective activation and synergistic bonding by a high-alkali system. The improvement of its cementing performance is subject to insurmountable physical property limitations. Simply increasing the lime content cannot address the essential mechanism of the "self-cementing" of this invention, nor can it break through the underlying limitations of its physical encapsulation.

[0005] Patent CN102381847A discloses a cementitious material composed of ordinary silicate cement clinker, water-quenched slag, anhydrite, and quicklime. Its cement clinker content is as high as 35-40%, essentially still belonging to a cement-based cementitious system. The production of clinker requires high-temperature calcination at 1450℃, resulting in high carbon emissions, which contradicts the low-carbon requirements of green mining. Furthermore, this technology uses anhydrite (anhydrous calcium sulfate) as the sulfate component. Anhydrite has a slow dissolution rate at room temperature, making it difficult to rapidly release sufficient SO4 in the early stages. 2- The reaction with the active aluminum phase to form ettringite limits the early strength development of the backfill. This scheme only treats the tailings as an inert filler and does not take into account activating the tailings' own activity to participate in the cementation.

[0006] Patent CN114656236A discloses a filling cementitious material comprising cement, granulated blast furnace slag powder, dihydrate gypsum, quicklime, and a chemical activator. While this method reduces cement usage, it still does not completely eliminate dependence on cement (which accounts for 5-40%), and requires the addition of 0.5-2% sulfate, chloride, or organic chemical activators. This application still uses blast furnace slag powder as the main cementing component, with tailings only used as diluent aggregate, failing to utilize the tailings' own activity in the cementing process.

[0007] There has long been an inherent technological bias in this field: it is generally believed that fine-grained tailings particles are small, have high impurity content, and low active component content, and can only be used as inert filler aggregates, unable to be activated and participate in the hydration cementation reaction. Existing filling technologies have all focused on improving the cementitious materials themselves, and have never proposed a technical approach to activate the activity of fine-grained tailings and achieve tailings self-cementation.

[0008] In summary, current market-available filling materials cannot simultaneously meet the engineering requirements of low cost, low carbon emissions, wide particle size compatibility, and high bonding strength. The industry urgently needs to develop a self-bonding filling material made entirely from industrial solid waste, which does not require high-temperature calcination and can break through traditional bonding mechanisms. Summary of the Invention

[0009] To address the aforementioned problems, namely the issues raised in the background art, this invention proposes a fine-grained tailings self-cementing backfill material synergistically activated by multi-source solid waste and its preparation method.

[0010] Technical solution The first aspect of this invention proposes a method for preparing a fine-grained tailings self-cementing backfill material synergistically activated by multi-source solid waste, comprising the following steps: S1. Preparation of cementitious material: Place water-quenched slag and desulfurized gypsum into a vacuum drying oven and dry until the material reaches constant weight. Crush into powder. Take 60-80 wt% water-quenched slag, 10-25 wt% desulfurized gypsum, and 5-15 wt% alkaline activator by mass fraction, and mix thoroughly to obtain a homogeneous composite cementitious material. XRF technology can be used to detect the chemical composition of the raw materials to ensure that the raw material quality meets the standards. S2. Preparation of self-cementing infill: Weigh fine-grained tailings, cementing material and water in a mass ratio of 1:6~10:0.3~0.4. The hydration reaction generates CSH gel and ettringite. After stirring evenly, the self-cementing infill is obtained.

[0011] A further setting of the present invention is that, in step S1, the drying temperature range is 55~65℃ and the drying time range is 12~24h.

[0012] A further provision of the present invention is that the alkaline activator is one or more combinations of quicklime, sodium sulfate, and caustic soda.

[0013] A further provision of the present invention is that, in S2, the hydration reaction specifically involves the active components in the cementitious material undergoing a hydration reaction with water. Quicklime provides an alkaline environment, which, together with the sulfate ions dissociated from the desulfurized gypsum, synergistically activates the pozzolanic activity on the surface of the water-quenched slag and fine-grained tailings particles. This allows the active silica-alumina components in the fine-grained tailings to directly participate in the reaction, generating hydration products primarily composed of CSH gel and ettringite. Through the dual consolidation effect of chemical bonding and physical filling of ettringite needle-like crystals, a strong interfacial bond is formed between the cementitious material and the fine-grained tailings, achieving self-cementing of the fine-grained tailings.

[0014] A further feature of the present invention is that the fine-grained tailings has a particle size of <0.35mm.

[0015] The second aspect of this invention proposes a self-cementing backfill material for fine-grained tailings that is synergistically activated by multiple solid waste sources: the raw materials include fine-grained tailings, cementing materials and water.

[0016] A further provision of the present invention is that the cementing material comprises: 60-80 wt% water-quenched slag, 10-25 wt% desulfurized gypsum, and 5-15 wt% alkaline activator; the preferred range of the cementing material is 65-75 wt% water-quenched slag, 15-20 wt% desulfurized gypsum, and 8-15 wt% alkaline activator; the optimal ratio determined by orthogonal experiment is 72 wt% water-quenched slag, 20 wt% desulfurized gypsum, and 8 wt% alkaline activator.

[0017] A further feature of the present invention is that the fine-grained tailings has a particle size of <0.35mm.

[0018] A further provision of the present invention is that the mass ratio of the fine-grained tailings, cementitious material, and water is 1:6~10:0.3~0.4.

[0019] A further provision of the present invention is that the alkaline activator is one or more combinations of quicklime, sodium sulfate, and caustic soda.

[0020] The beneficial technical effects of this invention are as follows: 1. Advanced cementing mechanism, excellent mechanical properties and structural stability: This invention breaks the industry's inherent perception of fine-grained tailings as inert aggregates and proposes for the first time the core concept of "self-cementing". It uses the alkaline environment formed by the hydrolysis of quicklime and the sulfate ions dissociated from the calcium source and desulfurized gypsum to build a high-alkali-sulfate synergistic activation system. This system simultaneously activates the pozzolanic activity on the surface of water-quenched slag and fine-grained tailings particles, causing the active silica-alumina components in the tailings to directly participate in the hydration reaction, generating CSH gel and needle-like ettringite. This forms Si-O-Al chemical bonds between the cementitious phase and the tailings particles, superimposed with the densification effect of ettringite crystals interpenetrating and filling, constructing a dual consolidation structure of chemical bonding and physical filling and coating. The particle interface bonding strength is greatly improved, overcoming the defects of traditional cement-based materials such as weak interface bonding, low early strength, and easy collapse when exposed to water. The overall structure of the filling body is dense, and there are problems such as no strength shrinkage and cracking during long-term curing. The mechanical performance indicators fully meet the standards of mine filling engineering.

[0021] 2. Green and low-carbon raw materials, high utilization rate of solid waste resources: The cementitious material of this invention uses bulk industrial solid waste such as water-quenched slag, desulfurized gypsum, and quicklime. Compared with traditional anhydrite, the rapid dissolution characteristics of desulfurized gypsum (dihydrate gypsum) can promote the early formation of ettringite. Traditional cement-based systems must undergo clinker calcination at temperatures above 1000 degrees Celsius. This invention completely eliminates the addition of cement clinker and avoids the high-temperature calcination process. It significantly reduces production energy consumption and carbon emissions, while also enabling large-scale disposal of industrial solid waste and fine-grained tailings from mines, achieving a "waste-to-waste" recycling model with significant ecological and environmental benefits.

[0022] 3. Low production cost and outstanding economic advantages: This invention uses inexpensive industrial solid waste as the core raw material, and the overall material cost is lower than that of ordinary silicate cement. At the same time, compared with the traditional cement backfill system, the invention requires a lower amount of cementitious material. Even with a low amount of cementitious material, the strength of the backfill body can still meet the engineering standards, effectively reducing the amount of cementitious material used and fundamentally reducing the overall cost of mine backfilling operations. This breaks through the dilemma of high cost and difficulty in large-scale promotion of traditional cement-based systems.

[0023] 4. Wide applicability and strong universality: Existing comparative patent CN112851286A uses only 4-5 wt% quicklime, which can only create a low-alkali and mild activation environment. It cannot reach the reaction threshold of destroying the aluminosilicate mineral skeleton of tailings and dissolving active silica-alumina components. It only relies on the physical encapsulation of ultrafine tailings smaller than 0.038 mm by hydration products. Once the tailings particles coarsen and the proportion of ultrafine particles decreases, the interparticle bonding strength is greatly reduced. It can only be used for special tailings with a very low proportion of ultrafine particles, and its application scenarios are very limited. Even if the lime content of this patent is artificially increased to 5-15 wt%, it still cannot activate the tailings themselves to achieve self-cementing. This invention precisely controls the quicklime content to 5-15 wt%, combined with desulfurized gypsum to continuously supply sulfate ions, constructing a high-alkali-sulfate synergistic activation system. This effectively overcomes the activation energy barrier of tailings minerals, allowing fine-grained tailings with different particle sizes and mineral compositions within the <0.35mm range to participate in the hydration reaction and form stable Si-O-Al chemical bonds. When a small amount of caustic soda and sodium sulfate are added, caustic soda can enhance the strong alkali erosion effect to break the inert coating on the tailings surface and accelerate the release of active silicon and aluminum ions, while sodium sulfate promotes the continuous dissociation of sulfate ions in the system. The two work synergistically to increase the formation of CSH gel and ettringite, further broadening the tailings adaptability range. This invention is not limited by the proportion of ultrafine particles in tailings and can be adapted to fine-grained tailings from various mines such as gold mines, iron mines, and non-ferrous metal mines. It also meets various engineering conditions such as underground goaf filling, surface tailings solidification, and layered backfilling. Compared with existing solidification technologies that are only applicable to ultrafine tailings, its engineering versatility is significantly improved.

[0024] 5. Simple construction process and strong practicality for promotion: The material mixing process of this invention is simple and does not require complex pretreatment processes such as flocculation sedimentation, high-pressure filtration, and vacuum dewatering for fine-grained tailings. It requires less equipment investment and occupies less space. It is convenient to prepare and construct and can be quickly applied in various mine sites, and has great engineering promotion value. Attached Figure Description

[0025] Figure 1 The SEM microstructure of the filling material prepared in Example 1 at 1 μm is shown.

[0026] Figure 2 The SEM microstructure of the filling material prepared in Example 1 at 2 μm is shown.

[0027] Figure 3 The XRD pattern of the filling material prepared in Example 1 is shown.

[0028] Figure 4 The Raman spectrum of the filling material prepared in Example 1 is shown.

[0029] Figure 5 The SEM microstructure of the filling material prepared in Example 2 at 1 μm is shown.

[0030] Figure 6 The SEM microstructure of the filling material prepared in Example 2 at 5 μm is shown.

[0031] Figure 7 The XRD pattern of the filling material prepared in Example 2 is shown.

[0032] Figure 8 The Raman spectrum of the filling material prepared in Example 2 is shown. Detailed Implementation

[0033] The following reference Figures 1-8 The preferred embodiments of the present invention will be described below. Those skilled in the art should understand that these embodiments are merely illustrative of the technical principles of the present invention and are not intended to limit the scope of protection of the present invention.

[0034] Example 1 This example uses fine-grained tailings from a mining area in Jilin Province as the research object to prepare backfill. The specific steps are as follows: S1. Preparation of cementitious material: Water quenched slag and desulfurized gypsum are placed in a vacuum drying oven and dried at 60°C for 12 hours until the material reaches constant weight. The material is then crushed into powder. By mass fraction, 72wt% of water quenched slag, 20wt% of desulfurized gypsum and 8wt% of quicklime are taken and thoroughly mixed to obtain a homogeneous composite cementitious material. S2. Preparation of self-cementing infill: Weigh fine-grained tailings, cementing material and water in a mass ratio of 1:8:0.35. The hydration reaction generates CSH gel and ettringite. After stirring evenly, the self-cementing infill is obtained. S3. Standard curing: The self-bonded infill body was cured for 3 days and 7 days at 25℃ and 95% humidity, respectively, and then subjected to uniaxial compressive strength test.

[0035] During the curing process of the filling material in this invention, the cementitious material undergoes a series of hydration reactions with water, and the core mechanism is as follows: ①: 2(3CaO·SiO2)+6H2O→3CaO·2SiO2·3H2O+3Ca(OH)2; ②: 2(2CaO·SiO2)+4H2O→3CaO·2SiO2·3H2O+Ca(OH)2; ③: 3CaO·Al2O3+3(CaSO4·2H2O)+26H2O→3CaO·Al2O3·3CaSO4·32H2O; Tricalcium silicate (3CaO·SiO2) and dicalcium silicate (2CaO·SiO2) in desulfurized gypsum react with water to form hydrated calcium silicate gel (CSH, 3CaO·2SiO2·3H2O) and calcium hydroxide (Ca(OH)2), as shown in reaction formulas ① and ②. CSH gel is the main cementing phase that imparts strength to the filling material, capable of encapsulating and binding the end sand particles to form a dense whole; calcium hydroxide provides a highly alkaline environment and provides a calcium source for subsequent initiation reactions.

[0036] Simultaneously, tricalcium aluminate (3CaO·Al2O3) in the desulfurized gypsum reacts with gypsum (CaSO4·2H2O) and water to form needle-like ettringite (3CaO·Al2O3·3CaSO4·32H2O), as shown in reaction formula ③. During the growth process, the ettringite crystals exhibit a micro-expansion effect, effectively filling the microscopic pores between the CSH gel and tailings particles, and interspersed within the gel network, playing an "anchoring" and "locking" role.

[0037] The three reactions described above work synergistically: the alkaline environment released by the hydrolysis of calcium hydroxide and quicklime further stimulates the active silica-alumina components in the water-quenched slag and the pozzolanic activity of the fine-grained tailings, promoting the formation of additional CSH gel and ettringite; the CSH gel provides a continuous bonding matrix, while ettringite enhances structural density and early strength through needle-like crystal penetration. This forms a dual consolidation mechanism of "chemical bonding + physical filling," significantly improving the interfacial bonding ability between cementitious materials and fine-grained tailings, solving the problems of poor adhesion, low early strength, and easy collapse upon contact with water in traditional cement-based materials and fine-grained tailings.

[0038] See Figure 1 and Figure 2 From the macroscopic morphology of the filling, it can be seen that there are many needle-like ettringite and hydrated calcium silicate gel-like substances inside the filling.

[0039] See Figure 3 As can be seen from the XRD pattern of the crystal structure of the filling, the main components of the filling are SiO2 and ettringite.

[0040] See Figure 4 As can be seen from the Raman spectrum, the formation of hydrated calcium silicate gel is beneficial to the strength of the filling body.

[0041] After curing for 3 days and 7 days respectively, uniaxial compressive strength tests were conducted on the filling material. The strength reached 1.46 MPa after 3 days and 2.41 MPa after 7 days, both meeting the engineering requirements.

[0042] Example 2 This example uses fine-grained tailings from a mining area in Sichuan Province as the research object to prepare backfill material. The specific steps are as follows: S1. Preparation of cementitious material: Water-quenched slag and desulfurized gypsum are placed in a vacuum drying oven and dried at 60°C for 12 hours until the material reaches constant weight. The material is then crushed into powder. By mass fraction, 67wt% water-quenched slag, 18wt% desulfurized gypsum, and 15wt% alkaline activator are taken. The alkaline activator by mass fraction is: 80wt% quicklime, 10wt% caustic soda, and 10wt% sodium sulfate. The mixture is thoroughly stirred to obtain a homogeneous composite cementitious material. S2. Preparation of self-cementing infill: Weigh fine-grained tailings, cementing material and water in a mass ratio of 1:8:0.3. The hydration reaction generates CSH gel and ettringite. After stirring evenly, the self-cementing infill is obtained. S3. Standard curing: The self-bonded infill body was cured for 3 days and 7 days at 25℃ and 95% humidity, respectively, and then subjected to uniaxial compressive strength test.

[0043] After curing for 3 days and 7 days respectively, uniaxial compressive strength tests were conducted on the filling material. The strength reached 2.3 MPa after 3 days and 3.47 MPa after 7 days, both meeting the engineering requirements.

[0044] See Figure 5 and Figure 6 From the macroscopic morphology of the filling, it can be seen that there are many needle-like ettringite and hydrated calcium silicate gel-like substances inside the filling.

[0045] See Figure 7 As can be seen from the XRD pattern of the crystal structure of the filling, the main components of the filling are SiO2 and ettringite.

[0046] See Figure 8 As can be seen from the Raman spectrum, the formation of hydrated calcium silicate gel is beneficial to the strength of the filling body.

[0047] Example 3 This example uses fine-grained tailings from a mining area in Sichuan Province as the research object to prepare backfill material. The specific steps are as follows: S1. Preparation of cementitious material: Water-quenched slag and desulfurized gypsum are placed in a vacuum drying oven and dried at 60°C for 12 hours until the material reaches constant weight. The material is then crushed into powder. By mass fraction, 67wt% water-quenched slag, 18wt% desulfurized gypsum, and 15wt% alkaline activator are taken. The alkaline activator by mass fraction is: 80wt% quicklime, 10wt% caustic soda, and 10wt% sodium sulfate. The mixture is thoroughly stirred to obtain a homogeneous composite cementitious material. S2. Preparation of self-cementing infill: Weigh fine-grained tailings, cementing material and water in a mass ratio of 1:10:0.3. The hydration reaction generates CSH gel and ettringite. After stirring evenly, the self-cementing infill is obtained. S3. Standard curing: The self-bonded infill body was cured for 3 days and 7 days at 25℃ and 95% humidity, respectively, and then subjected to uniaxial compressive strength test.

[0048] After curing for 3 days and 7 days respectively, uniaxial compressive strength tests were conducted on the filling material. The strength reached 1.55 MPa after 3 days and 1.98 MPa after 7 days, both meeting the engineering requirements.

[0049] Comparative Example 1: This example uses 425 cement as the sole component of the cementitious material and fine-grained tailings from a mining area in Jilin Province as the research object to prepare the backfill. The specific steps are as follows: S1. Preparation of cementitious materials: 425 grade ordinary Portland cement is used as cementitious materials, and no drying treatment is performed; S2. Preparation of self-cementing infill: Weigh fine-grained tailings, cement and water in a mass ratio of 1:8:0.4, mix them, and stir evenly to obtain the infill; S3. Standard curing: The filling body is cured for 3 days at a temperature of 25℃ and a humidity of 95%, and then a uniaxial compressive strength test is conducted.

[0050] The uniaxial compressive strength of the filling material after 3 days of curing was tested to be 1.74 MPa.

[0051] In Comparative Example 1, while the pure cement system achieves a certain early strength, its cementitious material cost is as high as approximately 500 yuan / ton, and cement production requires high-temperature calcination, resulting in carbon emissions of approximately 0.85t CO2 / t cement, placing a heavy environmental burden on the industry. In contrast, this invention uses industrial solid waste such as water-quenched slag as the main raw material, reducing costs by more than 90% compared to cement, and completely eliminating the high-temperature calcination process. While achieving similar or even superior cementing performance, it realizes significant economic and environmental benefits. Furthermore, pure cement has weak interfacial bonding with fine-grained tailings, making it prone to micro-cracks and strength reduction under long-term curing. This invention, through a dual consolidation mechanism of chemical bonding and ettringite filling, achieves a stronger interfacial bond and superior long-term structural stability.

[0052] Comparative Example 2: This example uses 425 cement as the sole component of the cementitious material and fine-grained tailings from a mining area in Jilin Province as the research object to prepare the backfill. The specific steps are as follows: S1. Preparation of cementitious materials: 425 grade ordinary Portland cement is used as cementitious materials, and no drying treatment is performed; S2. Preparation of self-cementing infill: Weigh fine-grained tailings, cement and water in a mass ratio of 1:10:0.35, mix them, and stir evenly to obtain the infill; S3. Standard curing: The filling body is cured for 3 days at a temperature of 25℃ and a humidity of 95%, and then a uniaxial compressive strength test is conducted.

[0053] The uniaxial compressive strength of the filling material after 3 days of curing was tested to be 0.68 MPa.

[0054] In Comparative Example 2, when the lime-sand ratio was reduced to 1:10, the 3-day strength of the pure cement system dropped significantly to 0.68 MPa, far below the self-supporting strength of over 1.0 MPa typically required for mine backfilling projects. In contrast, the present invention achieves 1.46 MPa at a lime-sand ratio of 1:8. If the lime-sand ratio of the present invention is adjusted to 1:10 (i.e., Example 3), its strength can still be maintained above 1.0 MPa due to the chemical activation and dual consolidation mechanism present in the system. This demonstrates that the present invention can ensure the backfill meets engineering strength requirements while significantly reducing the amount of cementitious materials used, whereas the pure cement system suffers from cementation failure due to insufficient cement content. This advantage stems from the present invention's use of quicklime to activate the activity of water-quenched slag and tailings, generating hydration products mainly composed of CSH gel and ettringite, achieving efficient cementation rather than solely relying on cement content.

[0055] Comparative Example 3: A fly ash-based alkali-activated cementitious material was used to prepare backfill material using fine-grained tailings from a mining area in Jilin Province. The specific steps are as follows: S1. Preparation of cementitious material: Place fly ash in a vacuum drying oven and dry it at 60°C for 12 hours until the material reaches constant weight. Crush it into powder. Take 65wt% fly ash, 20wt% quicklime, 5wt% sodium sulfate and 5wt% caustic soda by mass fraction. Mix them thoroughly to obtain a homogeneous composite cementitious material. S2. Preparation of self-cementing backfill: Weigh out fine-grained tailings, cementing material and water in a mass ratio of 1:6:0.35, mix them and stir evenly to obtain the backfill; S3. Standard curing: The filling body is cured for 3 days at a temperature of 25℃ and a humidity of 95%, and then a uniaxial compressive strength test is conducted.

[0056] Tests showed that the uniaxial compressive strength of the infill after 3 days of curing was less than 0.01 MPa, and the infill completely collapsed upon contact with water, failing to form an effective cemented structure.

[0057] A comparison between Comparative Example 3 and Example 1 of the present invention shows that, despite using a higher ash-to-sand ratio and various alkaline activators (quicklime, caustic soda, and sodium sulfate), the active silica-alumina components of its main raw material, fly ash, failed to be effectively released in the presence of fine-grained tailings, resulting in very little hydration product formation and an inability to form a continuous CSH gel or ettringite network. Furthermore, the strong alkalinity of caustic soda may cause excessive dispersion on the surface of tailings particles, disrupting effective contact between particles and ultimately leading to a filling material with no strength and disintegration upon contact with water. In contrast, the present invention uses water-quenched slag as the main raw material, combined with appropriate amounts of desulfurized gypsum and quicklime, to generate CSH gel and ettringite needle-like crystals through calcium silicate hydration, forming a dual-consolidation structure of chemical bonding and physical filling. Even with a lower ash-to-sand ratio, it still achieves high strength and excellent water stability, fully demonstrating the scientific nature and technological advancement of the present invention's formulation.

[0058] Comparative Example 4: A desulfurization ash-steel slag-based cementitious material was used to prepare backfill material, with fine-grained tailings from a mining area in Jilin Province as the research object. The specific steps are as follows: S1. Preparation of cementitious material: Desulfurization ash and steel slag are placed in a vacuum drying oven and dried at 60°C for 12 hours until the material reaches constant weight. They are then crushed into powder. According to the mass fraction, 40wt% of desulfurization ash, 40wt% of steel slag and 20wt% of quicklime are taken and thoroughly mixed to obtain a homogeneous composite cementitious material. S2. Preparation of self-cementing backfill: Weigh out fine-grained tailings, cementing material and water in a mass ratio of 1:4:0.35, mix them and stir evenly to obtain the backfill; S3. Standard curing: The filling body is cured for 3 days at a temperature of 25℃ and a humidity of 95%, and then a uniaxial compressive strength test is conducted.

[0059] Tests showed that the uniaxial compressive strength of the infill after 3 days of curing was less than 0.01 MPa, and the infill completely collapsed upon contact with water, failing to form an effective cemented structure.

[0060] A comparison between Comparative Example 4 and Example 1 of the present invention shows that although Comparative Example 4 uses a high ash-to-sand ratio and contains a certain amount of quicklime as an alkaline activator, the active components of its main raw materials, desulfurization ash and steel slag, are difficult to be effectively activated under normal temperature conditions. Desulfurization ash usually contains inert phases such as calcium sulfite, and the cementitious activity of steel slag is much lower than that of water-quenched slag. Neither can generate sufficient CSH gel and ettringite during hydration. Furthermore, the system lacks the early calcium silicate hydration reaction provided by desulfurization gypsum, resulting in slow initial setting of the system. After the quicklime hydration releases heat, it cannot form a continuous cemented network, ultimately causing the filling material to have no strength and collapse upon contact with water. In contrast, the present invention uses highly active water-quenched slag as the main raw material, combined with a suitable amount of desulfurization gypsum to provide an early hydration core, and supplemented with quicklime to regulate alkalinity and calcium source. The three work synergistically to generate abundant CSH gel and ettringite needle crystals, achieving high strength and excellent water stability at a low ash-to-sand ratio (1:8), fully demonstrating the scientific nature of the raw material selection and proportioning design of the present invention.

[0061] Comparative Example 5: To increase the amount of quicklime used, and to prepare backfill material using ultrafine-grained tailings from a mining area in Sichuan Province, the specific steps are as follows: S1. Preparation of cementitious material: Take tailings and screen them, retaining ultrafine tailings with a particle size of less than 0.038mm. Place water-quenched slag and desulfurized gypsum in a vacuum drying oven and dry them at 60℃ for 12h. Dry them until the material reaches constant weight, crush them into powder, and take 72wt% water-quenched slag, 20wt% desulfurized gypsum and 8wt% quicklime by mass fraction. Mix them thoroughly to obtain a homogeneous composite cementitious material. S2. Preparation of self-cementing backfill: Weigh fine-grained tailings, cementing material and water in a mass ratio of 1:8:0.35, mix them and stir evenly to obtain the backfill; S3. Standard curing: The filling body is cured for 3 days at a temperature of 25℃ and a humidity of 95%, and then a uniaxial compressive strength test is conducted.

[0062] Tests showed that the uniaxial compressive strength of the filling material after 3 days of curing was only 0.051 MPa, which does not meet the requirements for mine filling.

[0063] Comparative Example 5 shows that, under the condition of increasing the amount of quicklime, when the tailings are screened to the <0.038mm ultrafine particle size specified by patent CN112851286A, the strength decreases significantly and the structural integrity deteriorates markedly. The root cause is that the extremely high specific surface area and surface free energy of the ultrafine tailings in the strongly alkaline and high-calcium environment created by high lime content lead to severe interfacial kinetic mismatch. Instantaneous supersaturation precipitation on the particle surface forms a dense passivation layer, physically blocking the continuous dissolution of internal active silica-alumina components. Simultaneously, the high ionic strength exacerbates the soft agglomeration between ultrafine particles, destroying the initial packing density of the slurry and leading to the proliferation of microcracks in the interfacial transition zone. This result strongly demonstrates that the ultrafine particle size characteristic defined by patent CN112851286A has an intrinsic physicochemical conflict with the core activation system of this invention, and that there are insurmountable physical property limitations in improving its cementing performance. Patent CN112851286A cannot reach the essential mechanism of the "self-cementing" of this invention by simply increasing the amount of quicklime. Blindly increasing the lime content will lead to performance degradation due to system mismatch. This further confirms the inventiveness and non-obviousness of the synergistic design between the applicable range of tailings particle size (<0.35mm) and the high-alkali and high-sulfur synergistic activation system of this invention.

[0064] The above description is merely a preferred embodiment of the present invention, and the scope of protection of the present invention is not limited to the above embodiments. For those skilled in the art, any modifications, equivalent substitutions, or improvements made without departing from the technical concept of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a fine-grained tailings self-cementing backfill material synergistically activated by multi-source solid waste, characterized in that: Includes the following steps: S1. Preparation of cementitious material: Place water-quenched slag and desulfurized gypsum into a vacuum drying oven and dry until the material reaches constant weight. Crush into powder. Take 60-80 wt% water-quenched slag, 10-25 wt% desulfurized gypsum and 8-15 wt% alkaline activator by mass fraction, and mix thoroughly to obtain homogeneous composite cementitious material. S2. Preparation of self-cementing infill: Weigh fine-grained tailings, cementing material and water in a mass ratio of 1:6~10:0.3~0.

4. The hydration reaction generates CSH gel and ettringite. After stirring evenly, the self-cementing infill is obtained. In S2, the fine-grained tailings particle size is <0.35mm. The hydration reaction specifically involves the active components in the cementitious material undergoing a hydration reaction with water. Quicklime provides an alkaline environment, which, together with the sulfate ions dissociated from the desulfurized gypsum, synergistically activates the pozzolanic activity on the surface of the water-quenched slag and fine-grained tailings particles. This allows the active silica-alumina components in the fine-grained tailings to directly participate in the reaction, generating hydration products mainly composed of CSH gel and ettringite. Through chemical bonding and physical filling of ettringite needle-like crystals, a strong interfacial bond is formed between the cementitious material and the fine-grained tailings.

2. The preparation method of a fine-grained tailings self-cementing backfill material synergistically activated by multi-source solid waste according to claim 1, characterized in that: In S1, the drying temperature range is 55~65℃, and the drying time range is 12~24h.

3. The preparation method of a fine-grained tailings self-cementing backfill material synergistically activated by multi-source solid waste according to claim 1, characterized in that: The alkaline activator is one or more combinations of quicklime, sodium sulfate, and caustic soda.

4. A fine-grained tailings self-cementing backfill material prepared by the preparation method according to any one of claims 1-3, characterized in that: The raw materials include fine-grained tailings, cementing materials, and water.

5. The fine-grained tailings self-cementing backfill material synergistically activated by multi-source solid waste according to claim 4, characterized in that: The cementing material comprises: 60-80 wt% water-quenched slag, 10-25 wt% desulfurized gypsum, and 8-15 wt% alkaline activator.

6. The fine-grained tailings self-cementing backfill material synergistically activated by multi-source solid waste as described in claim 4, characterized in that: The fine-grained tailings have a particle size of <0.35mm.

7. The fine-grained tailings self-cementing backfill material synergistically activated by multi-source solid waste according to claim 4, characterized in that: The mass ratio of the fine-grained tailings, cementitious material, and water is 1:6~10:0.3~0.

4.

8. The fine-grained tailings self-cementing backfill material synergistically activated by multi-source solid waste as described in claim 5, characterized in that: The alkaline activator is one or more combinations of quicklime, sodium sulfate, and caustic soda.

Citation Information

Patent Citations

  • Mine-filling water-quenched blast furnace slag cementing material and preparation method thereof

    CN102381847A

  • Method for preparing underground cemented filling material by fully utilizing fine-fraction gold tailings

    CN112851286A

  • Gel material used for unclassified tailing cement

    CN102786241A